Effect of palm oil capsules on the self-healing properties of aged and unaged asphalt mixtures gained by resting period and microwave heating. (17th January 2022) - Kargari, Amirhossien; Arabani, Mahyar; Mirabdolazimi, Seyyed Mohammad
Graphical abstract: Abstract: Palm oil was used as a new rejuvenating agent for manufacturing calcium alginate capsules to study the self-healing properties of aged and unaged asphalt mixtures. To optimize the palm oil capsule for use in the asphalt mixture, nine types of calcium alginate capsules with various oil-to-water (O/W = 5, 10, and 15 %w) and calcium chloride-to-water percentages (CaCl2 /W = 2, 4, and 6 %w) were prepared, and compressive strength, thermal sensitivity, size measurement, density measurement, scanning electron microscopy (SEM), and thermogravimetric analysis (TGA) tests were performed on them. Asphalt mixtures with various percentages of optimum capsules (0, 0.35, and 0.7% by total weight of the mixture) were prepared in unaged and long-term-aged conditions, and the effect of capsules on the stiffness modulus of aged and unaged asphalt mixtures was investigated by the indirect tensile stiffness modulus (ITSM) test. Via the semicircular bending (SCB) test, self-healing with a resting period and microwave healing were used to investigate the self-healing properties of aged and unaged asphalt mixtures with and without capsules. To reduce heating time and energy consumption, the effect of incorporating steel wool fibers (SWF) on the microwave heating of palm oil capsule-containing asphalt mixtures was investigated. The results showed that the use of palm oil capsules significantly increased the self-healing capability of the aged and unaged asphalt mixtures. The microwave healing method promoted the healing speed and healing level of the capsule-containing aged and unaged asphalt mixtures. Moreover, with the use of SWF in microwave healing, a healing level similar to that of SWF-less asphalt specimens was obtained in a shorter heating time.